Effect of marriage on outcomes for elderly patients with head and neck cancer. Issue 5 (18th June 2014) - Schaefer, Eric W.; Wilson, Matthew Z.; Goldenberg, David; Mackley, Heath; Koch, Wayne; Hollenbeak, Christopher S.
Abstract: Background: Beneficial effects of marriage on cancer outcomes have been observed for many cancers, but oral cavity and pharyngeal cancers have never been examined. Methods: We used the National Cancer Institute (NCI) Surveillance, Epidemiology, and End Results (SEER) Program linked with Medicare records to identify 9403 elderly patients (age ≥66 years) with oral cavity and pharyngeal cancers. We used a propensity score analysis to estimate differences in proportions (pd ) between married and unmarried patients on stage, treatment, and survival. Results: For oral cavity cancers, a larger proportion of married patients presented with earlier stage (pd = 0.05; 95% confidence interval [CI], 0.02–0.08), were treated with surgery (pd = 0.06; 95% CI, 0.03–0.08), and survived 1 year (pd = 0.04; 95% CI, 0.01–0.06). Similar results were found for pharyngeal cancers for stage (pd = 0.04; 95% CI, 0.01–0.06), treatment with chemotherapy and radiation (pd = 0.04; 95% CI, 0.01–0.07), and 1‐year survival (pd = 0.01; 95% CI, 0.08–0.16). Conclusion: Marriage is associated with earlier stage, aggressive treatment, and superior survival for patients with oral cavity and pharyngeal cancers. © 2014 Wiley Periodicals, Inc. Head Neck 37: 735–742, 2015